2014
DOI: 10.2166/wrd.2014.058
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of water reuse and desalination: a review of greenhouse gas emissions and estimation tools

Abstract: As population and water demand increase, there is a growing need for alternative water supplies from water reuse and desalination systems. These systems are beneficial to water augmentation; however, there are concerns related to their carbon footprint. This study compiles the reported carbon footprint of these systems from existing literature, recognizes general trends of carbon footprint of water reuse and desalination, and identifies challenges associated with comparing the carbon footprint. Furthermore, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 3 publications
0
41
1
1
Order By: Relevance
“…The environmental impact of water desalination has been focused on theoretical and scenario analyses [5]. Cornejo et al [6] found that reverse osmosis (RO) technologies have lower GHG emissions than thermal desalination technologies. The estimated GHG emissions footprint of seawater RO desalination (0.4-6.7 kg CO 2eq /m 3 ) is generally larger than brackish water RO desalination (0.4-2.5 kg CO 2eq /m 3 ) and water reuse systems (0.1-2.4 kg CO 2eq /m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental impact of water desalination has been focused on theoretical and scenario analyses [5]. Cornejo et al [6] found that reverse osmosis (RO) technologies have lower GHG emissions than thermal desalination technologies. The estimated GHG emissions footprint of seawater RO desalination (0.4-6.7 kg CO 2eq /m 3 ) is generally larger than brackish water RO desalination (0.4-2.5 kg CO 2eq /m 3 ) and water reuse systems (0.1-2.4 kg CO 2eq /m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ve phases of the evaluated SWRO process are seawater pumping and intake, pretreatment, reverse osmosis operation, post treatment and water storage and distribution. Figure 3 shows the total carbon footprint of 3.5 × 10 −2 kg CO 2 -eq/year, with the assumption that the contribution was not signi cant and way smaller than the reported values of 1.599-5.63 kg CO 2 -eq for Spain, 2.208-7.46 kg CO 2 -eq for Israel, 2.562 kg CO 2 -eq for China, and 2.1-3.6 kg CO 2 -eq for Singapore (Pablo et al 2014;Jiahong Liu et al 2015;Biswas et al 2016;Xuexiu Jia et al 2019). The other contributing factors are plant capacity, adaptation of technology, fuel type, and the selection of attribute calculation in scopes 1, 2, and 3.…”
Section: C0 2-eq Emissions In the Operation Processmentioning
confidence: 64%
“…In addition, the CF results can be meaningful if this approach is integrated with other indicators and attributes such as energy and water. Also, several carbon footprint evaluation instruments such as WESTWeb model, CHEApet, Simulation Platform No.2 (BSM2G), Johnston tools, LCA hybrid tools and other equipment can estimate more accurately (Pablo et al 2014). As mentioned earlier, SWRO sustainability is related to the alternative selection to minimise environmental impact, and the integration between the different sources of energy with a renewable energy was fundamentally selected to meet the objective.…”
Section: Relationship Between Limitations Strategies and Adaptionmentioning
confidence: 99%
“…The study also assessed the performance of the local utility's centralized wastewater treatment plant, which was found to be significantly more efficient than the LM. The life-cycle approach was adopted for cases in which the specification of the environmental variable required a systemic scope [4][5][6][7][8][9][10][11]. Morera et al [4] applied the Water Footprint to assess the consumption of water resources in wastewater treatment plants (WWTP).…”
Section: Introductionmentioning
confidence: 99%